Answers

2015-06-25T14:05:00+05:30
Y-1/y=9
(y-1/y)² = y² + (1/y)² - 2
(9)²+2 = y² + (1/y)²= 83


(y²+1/y²) = y^4+1/y^4+2
(83)²=y^4+1/y^4+2
y^4+1/y^4=6889-2
y^4+1/y^4=6887
if i helped then say thanx and mark my answer as best if it is
0
  • Brainly User
2015-06-25T14:05:55+05:30
You've got y-\frac{1}{y} = 9.
Square it, y^{2}+\frac{1}{y^2}-2=81 \Rightarrow y^{2}+\frac{1}{y^2}=83.
Raise the power to four, y^4 - 4y^2 + 6 - 4\frac{1}{y^2} + \frac{1}{y^4} = 6561 \\ \Rightarrow y^4 + \frac{1}{y^4} + 6 - 4(83) =6561 \\
\Rightarrow y^4 + \frac{1}{y^4} = 6887.
0